Factors Responsible for Choice of FMCG Products:A Case Study of the Consumers of Dental Care Products - Bhattacharyya, Pinaki Ranjan; Mazumdar, Sitanath (Indian Journal of Marketing, 2009)
The economic growth in India has changed consumer’s taste and selection process while deciding on the purchase of a particular product or service. While purchasing a particular product, a consumer tries to match all the possible options that he is looking for in the product but finds that he is not fully satisfied with the product or service. The implicit consumer attitude becomes more imminent, particularly in the case of FMCG products where the price variation is very less for different brands. So there exists a gap between the expected need of the consumer and the product procured by him. This gap can be narrowed down if a line can be drawn about the factors affecting the consumers towards choice of FMCG products. The present research has been carried out with 150 respondents and 20 retailers in and around Kolkata with an objective to explore and understand the orientation of a consumer towards a particular brand and also the different factors that affect his perception for a particular brand, in the Indian context, with reference to the Dental Care Products.